Ab initio prediction of a silicene and graphene heterostructure as an anode material for Li- and Na-ion batteries. Issue 42 (6th October 2016) - Shi, L.; Zhao, T. S.; Xu, A.; Xu, J. B.
Abstract : The heterostructure of silicene and graphene can serve as a promising anode material for lithium- and sodium-ion batteries. Abstract : Silicene has been predicted to be an extraordinary anode material for lithium-ion batteries with a large capacity and low lithium migration energy barriers, but the free-standing form of silicene is unstable, virtually requiring a substrate support. In this work, we propose to use graphene as a substrate and a protective layer of silicene, forming a van der Waals heterostructure of silicene and graphene (Si/G) to serve as a prospective anode material for lithium/sodium-ion batteries. Ab initio calculations show that the Si/G heterostructure not only preserves the silicene's large lithium/sodium capacity (487 mA h g −1 ) and low lithium/sodium migration energy barriers (<0.4 eV for lithium and <0.3 eV for sodium), but also provides much larger lithium/sodium binding energies via a synergistic effect, which can effectively inhibit the formation of dendrites. Density of states results show that the Si/G heterostructure is metallic before and after lithium/sodium intercalation, ensuring a good electronic conductivity. In addition, the mechanical stiffness of the Si/G heterostructure is found to be larger than that of pristine silicene or graphene, which helps preserve the structural integrity and enhance the cycle performance.